Positive short-term subjective effect of sports drink supplementation during recovery - Fahlström, M.; Fahlström, P. G.; Lorentzon, R.; Henriksson-Larsen, K. (The Journal of Sports Medicine and Physical Fitness, 2006)
Aim: The aim of this study was to investigate the effects of a naturally composed sports drink containing proteins and carbohydrates used during recovery in competitive badminton players. The hypothesis was that the use of a recovery drink would lead to positive subjective effects, enhanced physical performance and less signs of overtraining. Methods: During an in-door season 18 badminton players were instructed to drink at least 250 mL of a given sports drink immediately after each training or playing session. The study design was prospective double blind crossover with one active drink and one placebo. The active drink was based on natural products containing whey and orange juice, and the placebo was made of diluted apple juice. Evaluation of effects was done with laboratory tests, self-registered values and field tests. Results: The players perceived statistically significant short-term subjective positive effects after using the active drink, compared with after using placebo. The blood hemoglobin concentration was also higher after the period with active drink. There were no other differences concerning other laboratory tests (leg strength, endurance, body fat percent, lean arm and leg masses), self-registered values (body weight, pulse, training amount and intensity) or field tests (speed, explosive effort, grip strength, endurance and POMS) between the periods with the different sports drinks. Conclusions: Supplementation with a sports drink during recovery showed a significant short-term subjective positive effect compared with placebo. However, no effects were seen on physical performance or signs of overtraining.